Recent creative innovations for modernizing traditional medicine - Ghazaleh Mosleh; Abdolali Mohagheghzadeh (Shiraz University of Medical Sciences, 2022)
< p>Traditional medicine with a profound historical background is a rich source of clinical experiences for thousands of years. It has shown promising therapeutic effects on complex disorders with a holistic approach. However, the multi-component and multi-target pharmacology of traditional drugs are not clearly understood with the current reductionist approach. Modernization of traditional medicine (TM) by means of modern technology and academic thoughts as well as innovative methods and scientific experiments helps better perception of the ancient wisdom behind traditional mechanisms. Besides, modernization of TM via new ideas from the globally accepted scientific standards can result in a series of highly active, safe, and controllable modern TM products. In this approach, advanced technology and innovative methodology play a key role in TM development. On the other hand, personalized medicine paradigm which is recommended in TM theories aims to achieve the proper diagnosis and treatment for each patient. It particularly focuses on the maintenance of health and enhancing the resistance of body to diseases. The present work was conducted to emphasis the pivotal role of utilizing modern innovations in TM systems